2004
DOI: 10.1152/ajpregu.00352.2003
|View full text |Cite
|
Sign up to set email alerts
|

Acute arterial hypertension inhibits proximal tubular fluid reabsorption in normotensive rat but not in SHR

Abstract: Walstead, Christopher, and Kay-Pong Yip. Acute arterial hypertension inhibits proximal tubular fluid reabsorption in normotensive rat but not in SHR. Am J Physiol Regul Integr Comp Physiol 286: R726-R733, 2004. First published December 24, 2003 10.1152/ ajpregu.00352.2003.-The effect of acute arterial hypertension on proximal tubular fluid reabsorption was investigated in SpragueDawley rats and spontaneously hypertensive rats (SHR) by measuring proximal tubular flow with a nonobstructive optical method. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…An acute rise in renal arterial pressure not only increases single nephron GFR but also induces a progressive reduction of proximal tubular reabsorption (34,67,107,204). The increase of fluid remaining in the distal tubule will add to the tubular load entering the loop of Henle and thereby enhance the error signal reaching the macula densa.…”
Section: Autoregulatory Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…An acute rise in renal arterial pressure not only increases single nephron GFR but also induces a progressive reduction of proximal tubular reabsorption (34,67,107,204). The increase of fluid remaining in the distal tubule will add to the tubular load entering the loop of Henle and thereby enhance the error signal reaching the macula densa.…”
Section: Autoregulatory Mechanismsmentioning
confidence: 99%
“…Accordingly, a progressive reduction of reabsorption will slowly augment the regulatory strength of TGF (132). Although the pressuredependent modulation of proximal tubular reabsorption may stretch out over a course of 20 -30 min after the change in pressure, the majority of this adaptation seems to occur within the initial 5 min (34,204,222). Furthermore, the change in reabsorption has been found to be associated with a redistribution of Na ϩ -H ϩ -transporter (NHE3), Na ϩ -phosphate-cotransporter (NaPi2) in the proximal tubular epithelium from the tip of the apical brush border to the base of the villi and finally to intracellular vesicles, and accompanied by a reduction in Na ϩ -K ϩ -ATPase activity (124,127,222).…”
Section: Autoregulatory Mechanismsmentioning
confidence: 99%
“…Thus renal factors are likely to be predominant in the altered pressure natriuresis in LH rats. The intra-renal alterations can be numerous such as an enhanced proximal tubular fluid reabsorption [18], a deficit in renal nitric oxide activity [19] and an alteration in renal medullary blood flow [20]. We previously observed that in LH rats, the reduced urinary sodium excretion was associated with a lack of medullary blood flow increase in response to arterial pressure elevations [8] and an altered medullary blood flow response to angiotensin II [21].…”
Section: Lh (N = 8)mentioning
confidence: 99%
“…5). The imaging system used for detecting DAF-FM emission from proximal tubule is similar to that used for detecting BCECF emission as described previously (20,22). Uncaging of NO in luminal perfusate was achieved by delivering the laser pulses to the kidney surface via an optical fiber.…”
Section: Discussionmentioning
confidence: 99%
“…This prediction has been verified using EIPA to inhibit apical Na ϩ /H ϩ exchanger in the proximal tubule of free-flow nephron. Intratubular perfusion of EIPA into the proximal tubule decreases proximal tubular flow when TGF is intact, and the same maneuver increases proximal tubular flow when TGF is inhibited by furosemide (20). cGMP is the mediator of NO to inhibit proximal tubular reabsorption (4).…”
Section: Discussionmentioning
confidence: 99%